2017
DOI: 10.1515/cpp-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and the risk of Internet addiction in teenagers aged 13-17 years living in the urban and rural areas

Abstract: Alcohol consumption and the risk of Internet addiction in teenagers aged 13-17 years living in the urban and rural areasSpożywanie alkoholu a zagrożenie uzależnieniem od Internetu u młodzieży w wieku od 13 do 17 roku życia mieszkającej w mieście i na wsi Maciej Zygo 1 B,E,F,G, Emilia Potembska 2 A,C,D,E,F,G, Karol Zygo 3 B,E, Andrzej Stanisławek 4 E,F, Łukasz Karaś 5 E,F, Beata Pawłowska 6 A,C,D,E,F,G AbstractThe aim of this paper was to determine differences and similarities between city dwelling teenagers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
(53 reference statements)
2
6
0
Order By: Relevance
“…16,17,[46][47][48][49] There are other studies indicating that substance use, smoking, and alcohol use are higher in individuals with internet addiction. 12,35,36,50 The findings of the study are consistent with those of the literature.…”
Section: Discussionsupporting
confidence: 91%
“…16,17,[46][47][48][49] There are other studies indicating that substance use, smoking, and alcohol use are higher in individuals with internet addiction. 12,35,36,50 The findings of the study are consistent with those of the literature.…”
Section: Discussionsupporting
confidence: 91%
“…A study carried out in 2017 among 1191 young people by means of the Internet Addiction Questionnaire highlighted the connection between risky IAD-related behaviours and alcohol consumption. The correlation between online and offline risky behaviours is also visible in the area of Internet pornography and gaming, and regular alcohol consumption by minors correlates with high results in tests measuring IAD [56]. We find slightly different results in a study conducted in 2015 by a Warsaw team who used Young's Diagnostic Questionnaire (YDQ).…”
Section: International Research Results On Piumentioning
confidence: 63%
“…Prior research has found associations between alcohol use and problematic Internet use among adolescents (Gámez-Guadix et al, 2015; Golpe et al, 2017; Morioka et al, 2017; Zygo et al, 2017). This relationship is likely indicative of an underlying vulnerability to addictive behaviors among some adolescents; however, little is known about specific factors that may increase this vulnerability.…”
mentioning
confidence: 99%
“…The coexistence of alcohol use with other risky behaviors is a recognized public health problem (Kumar et al, 2015; Lee et al, 2013; Morioka et al, 2017; Zygo et al, 2017). More recently, researchers have examined the co-occurrence of alcohol use and problematic Internet use among adolescents (Demirer & Bozoglan, 2016; Golpe et al, 2017; Morioka et al, 2017; Zygo et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation